The Microbiological Quality of Raw Ovine Milk in the Banat Region of Romania with a Focus on Escherichia coli and Its Pathogenic Potential and Antimicrobial Resistance - Răzvan-Dragoș Roșu; Adriana Morar; Alexandra Ban-Cucerzan; Mirela Imre; Khalid Ibrahim Sallam; Al-Ashmawy A. Maha; Samir Mohammed Abd-Elghany; Sebastian Alexandru Popa; Răzvan-Tudor Pătrînjan; Doru Morar; Kálmán Imre (Veterinary Sciences)
This study investigated the bacteriological quality of raw ovine milk produced by farms located in the Banat region of Romania. Additionally, the pathogenic potential and antimicrobial resistance of the isolated Escherichia coli strains were evaluated. A total of 95.8% (69/72) of the screened bulk tank milk samples, collected at the farm level immediately after milking, demonstrated appropriate total aerobic mesophilic bacteria (TMB) counts, varying from 3.32 to 6.09 log10 CFU/mL. However, 4.2% (3/72) of the samples were above the regulatory limit of 6.18 log10 CFU/mL. E. coli was identified in 66.6% of the examined samples, and from the total number (n = 48) of isolates, 18.8% harbored the stx2 gene, highlighting pathogenic potential. Antimicrobial susceptibility testing with the Vitek2 system of the isolated E. coli strains revealed resistance against ampicillin (45.8%), gentamicin (20.8%), ticarcillin–clavulanic acid (18.8%), cephalexin (18.8%), amoxicillin–clavulanic acid (8.3%), and trimethoprim–sulfamethoxazole (2.1%). Additionally, 64.6% of the strains showed intermediate resistance against amoxicillin–clavulanic acid, while no resistance was recorded against imipenem. Five (18.5%) strains were multidrug-resistant. This study’s results underline hygienic sanitary deficiencies during the milking phase and indicate that raw ovine milk can be contaminated with pathogenic and multidrug-resistant E. coli strains, highlighting a potential risk to public health. Further studies are encouraged to better understand the risk posed to the consumer via the consumption of ovine milk and derived products.